Crosstalk Between Autophagy and Ferroptosis and Its Putative Role in Ischemic Stroke - Liu, Jie; Guo, Zhen-Ni; Yan, Xiu-Li; Huang, Shuo; Ren, Jia-Xin; Luo, Yun; Yang, Yi (Frontiers in Cellular Neuroscience, 2020)
Autophagy is a conserved process to maintains homeostasis via the degradation of toxic cell contents, which can either promote cell survival or accelerate cellular demise. Ferroptosis is a recently discovered iron-dependent cell death pathway associated with the accumulation of lethal reactive lipid species. In the past few years, an increasing number of studies have suggested the crosstalk between autophagy and ferroptosis. Ischemic stroke is a complex brain disease regulated by several cell death pathways, including autophagy and ferroptosis. However, the potential links between autophagy and ferroptosis in ischemic stroke have not yet been explored. In this review, we briefly overview the mechanisms of ferroptosis and autophagy, as well as their possible connections in ischemic stroke. The elucidation of crosstalk between different cell death pathways may provide insight into new future ischemic stroke therapies.